2002
DOI: 10.1175/1520-0485(2002)032<0573:lswtbp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Labrador Sea Water Tracked by Profiling Floats—From the Boundary Current into the Open North Atlantic

Abstract: Fifteen profiling floats were injected into the deep boundary current off Labrador. They were ballasted to drift in the core depth of Labrador Sea Water (LSW) at 1500-m depth and were deployed in two groups during March and July/August 1997. Initially, for about three months, the floats were drifting within the boundary current, and the flow vectors were used to determine the mean horizontal structure of the Deep Labrador Current, which was found to be about 100 km wide with an average core speed of 18 cm s Ϫ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 17 publications
7
79
0
Order By: Relevance
“…8a). Although the simulated pathway of the LSW in our model is far too eastward, the same mechanism may also hold in more realistic circumstances, such as near the Grand Banks where the deep water splits into two branches, one moving southward along the western boundary and the other entering the eastern North Atlantic basin (Fischer and Schott 2002).…”
Section: Summary and Discussionmentioning
confidence: 67%
“…8a). Although the simulated pathway of the LSW in our model is far too eastward, the same mechanism may also hold in more realistic circumstances, such as near the Grand Banks where the deep water splits into two branches, one moving southward along the western boundary and the other entering the eastern North Atlantic basin (Fischer and Schott 2002).…”
Section: Summary and Discussionmentioning
confidence: 67%
“…Previous Lagrangian studies of the DWBC at this location [17] [35] show that floats exited the DWBC almost immediately, but this result was surprising given the convention that the DWBC was the dominant export pathway for the deep limb of the AMOC. The debate in the oceanographic community turned to whether or not the profiling floats used in these studies, which came to the surface about once every 10 days, were able to reliably track the Lagrangian pathways of true water parcels.…”
Section: The Behavior Of Trajectories Exiting the Dwbcmentioning
confidence: 82%
“…Fischer and Schott (2002) eventually travel south, most did it via an interior pathway. It is important to mention that both these studies took place during weak to no-convection conditions in the Labrador Sea (Yashayaev (2007)).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Swallow and Worthington (1961), Schott et al (2004), Pickart and Smethie (1998), Joyce et al (2005), Toole et al (2010)), reinforcing the existing view of a continuous DWBC that connects the northern North Atlantic and the subtropics. But more recently, Fischer and Schott (2002) float ob-servations, and later work by Bower et al (2009), both with float trajectories and numerical simulations, suggested that a larger fraction of the LSW that reaches the subtropics does so via an interior pathway. The DWBC played, according to these authors, a secondary role in the export of LSW, mostly due to the eddy variability, unresolved in coarse resolution models.…”
Section: Introductionmentioning
confidence: 99%